Perspective of enhancing wheat production and productivity in Uttar Pradesh by improving varietal replacement rate - Sharma, Amit Kumar; Mishra, Chandra Nath; Singh, Bishnu Partap; Singh, Sanjay Kr; Singh, Gyanendra Pratap (Journal of Cereal Research, 2025)
Uttar Pradesh is the largest wheat producing state in the country which has very variable agro-ecological production conditions. Being largest state in acreage, it has several constraints to wheat production but strategic enhancement of varietal replacement rate through supply of seed of improved varieties of wheat in UP has played important role in enhancing production, productivity and replacing old wheat varieties from seed chain. There is still scope of adoption of more improved varieties released in recent past with combined synergy among research institutions, state department of agriculture, extension workers and seed producing agencies which can make UP a highest productive state of wheat.DOI.10.25174/2582-2675/2020/100826